Penerapan Rapid Application Development Dan Model Kano Dalam Pengembangan Sistem Informasi Geografis - Samsuri Yahya; Fajar Mahardika (STMIK Banjarbaru, 2023)
The high intensity of incoming reports by members and volunteers of Garda Animalia (a non-governmental organization that deals with Wildlife) through various social media platforms has made it difficult for management to map and recapitulate incoming reports. Making a map of the spread of protected wildlife crime with each category also still takes quite a long time to report the incident. This research develops a geographic information system model for mapping and fault control of protected fauna. The system is designed using the Rapid Application Development method and the Kano model to speed up the system analysis and development process. Analysis of user needs is carried out by involving the user directly, including in system design. The test results show that the animal crime reporting process can be carried out through a one-stop channel, data recapitulation only takes a short time, and distribution maps can be made automatically.Keywords: Rapid Application Development; Kano Model; Geographical Information System; Protected Wildlife Crime AbstrakTingginya Intensitas pelaporan yang masuk dari anggota dan relawan Garda Animalia (sebuah Lembaga Swadaya Masyarakat yang mengurusi Satwa Liar) melalui berbagai platform media sosial, menyebabkan pihak manajemen kesulitan untuk melakukan pemetaan serta rekapitulasi laporan yang masuk. Pembuatan peta persebaran kejahatan satwa liar dilindungi dengan masing-masing kategori juga masih membutuhkan waktu cukup lama dalam pelaporan kejadian tersebut. Penelitian ini mengembangkan model sistem informasi geografis untuk pemetaan dan kontrol perbuatan kesalahan Fauna dilindungi. Sistem dirancang dengan metode Rapid Application Development dan model Kano untuk mempercepat proses analisis dan pengembangan sistem. Analisa kebutuhan user dilakukan dengan melibatkan langsung user, termasuk dalam perancangan sistem. Hasil uji menunjukkan proses pelaporan kejahatan satwa dapat dilaukan melalui jalur satu pintu, rekapitulasi data hanya membutuhkan waktu singkat, serta pembuatan peta persebaran dapat dilakukan secara otomatis.Kata kunci: Rapid Application Development; Model Kano; Geografical Information System; Kejahatan Satwa Liar Dilindungi